Criminal Action of Spreading Fake News - Tri Julita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The rise of the crime of spreading false news in the last two years has increased sharply. The data released by the Directorate of Cyber Crime for handling cases of spreading notifications and/or fake news has increased sharply. The crime of spreading false and misleading news is also contained in Article 390 of the Criminal Code, only in that article there is the phrase "broadcasting false news". In this crime, the means used are electronic media. Internet is one of the facilities used through electronic media. Based on Law Number 11 of 2008 Article 28 paragraph (1) concerning Information and Electronic Transactions states that everyone intentionally and without rights spreads false and misleading news that results in consumer losses in electronic transactions. The purpose of writing this journal is to explain and examine accountability in the crime of spreading false and misleading news, to find out the responsibility for the criminal act of spreading false and misleading news based on Law Number 11 of 2008.